Shorter Clopidogrel Therapy Not Superior following Coronary DES Implantation - Hoyle, Brian (MD Conference Express, 2014)
In the Triple Therapy in Patients on Oral Anticoagulation After Drug Eluting Stent Implantation trial [ISAR-TRIPLE; NCT00776633], 6 weeks of triple therapy including the oral antiplatelet compound clopidogrel is not superior to a 6-month regimen following implantation of a drug-eluting stent.